2021
DOI: 10.1111/aogs.14252
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 infection in pregnancy in Denmark—characteristics and outcomes after confirmed infection in pregnancy: A nationwide, prospective, population‐based cohort study

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 18 publications
5
37
2
1
Order By: Relevance
“…It has been shown that the risk of preterm birth and perinatal death may be increased in hospitalised pregnant women with COVID‐19 18 . This was also found in a Nordic study that included data from Denmark, 19 but until October 2020, we have data that show that only a few pregnant women were admitted to Danish hospitals due to COVID‐19 20 . Another study found that most of the preterm births in pregnant women with COVID‐19 were iatrogenic 21 .…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…It has been shown that the risk of preterm birth and perinatal death may be increased in hospitalised pregnant women with COVID‐19 18 . This was also found in a Nordic study that included data from Denmark, 19 but until October 2020, we have data that show that only a few pregnant women were admitted to Danish hospitals due to COVID‐19 20 . Another study found that most of the preterm births in pregnant women with COVID‐19 were iatrogenic 21 .…”
Section: Discussionsupporting
confidence: 76%
“…18 This was also found in a Nordic study that included data from Denmark, 19 but until October 2020, we have data that show that only a few pregnant women were admitted to Danish hospitals due to COVID-19. 20 Another study found that most of the preterm births in pregnant women with COVID-19 were iatrogenic. 21 It is possible that a small change in interventions by professionals might have influenced the association between COVID-19 and preterm births.…”
Section: Discussionmentioning
confidence: 99%
“…We obtained demographic and clinical data of participants as well as non‐participants in the “CareMum COVID‐19 study” from the Danish “COVID‐19 in pregnancy” database, which contains information based on medical records on all women with confirmed SARS‐CoV‐2 infection during pregnancy in Denmark, as described elsewhere. 12 Case completeness of the database was secured by a retrospective registry linkage to national databases containing information on positive SARS‐CoV‐2 tests. Furthermore, participants were asked to complete a questionnaire about COVID‐19 symptoms at the time of inclusion.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence of poor maternal and infant outcomes from past outbreaks of viral respiratory illness, including the coronaviruses SARS 1,2 and Middle East respiratory syndrome (MERS), 3 as well as 2009 influenza A(H1N1), 4,5 suggested that SARS-CoV-2 may also differentially affect pregnant individuals. However, international reports have been varied in the degree of illness severity resulting from SARS-CoV-2 infection [6][7][8][9][10][11][12][13][14][15] and the degree and nature of associated adverse pregnancy outcomes, such as preeclampsia, preterm birth, stillbirth, and cesarean delivery. [8][9][10][11]14 Since existent studies are highly heterogeneous, with many including only cases of COVID-19 identified at the time of hospital admission for obstetric delivery, they may not adequately represent the full effect of SARS-CoV-2 on pregnant populations, which includes infection acquired throughout pregnancy and a range of disease severity.…”
mentioning
confidence: 99%